2022
DOI: 10.3982/ecta17433
|View full text |Cite
|
Sign up to set email alerts
|

Global Banks and Systemic Debt Crises

Abstract: We study the role of global financial intermediaries in international lending. We construct a model of the world economy, in which heterogeneous borrowers issue risky securities purchased by financial intermediaries. Aggregate shocks transmit internationally through financial intermediaries' net worth. The strength of this transmission is governed by the degree of frictions intermediaries face in financing their risky investments. We provide direct empirical evidence on this mechanism showing that around Lehma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 81 publications
2
17
0
Order By: Relevance
“…Panel (a) of Table 4 reports that the estimated coefficient for γ is negative and statistically significant, which indicates that within a firm, bonds that have more substantial holdings by the intermediary releasing earnings have a larger sensitivity in absolute value to financial shocks. These results are consistent with financial shocks' having an effect on the security prices of nonfinancial firms through financial intermediaries' net worth, which under short-run trading frictions can translate into different prices for bonds with similar risk (see Morelli et al, 2021).…”
Section: Robustness and Placebo Testssupporting
confidence: 78%
See 1 more Smart Citation
“…Panel (a) of Table 4 reports that the estimated coefficient for γ is negative and statistically significant, which indicates that within a firm, bonds that have more substantial holdings by the intermediary releasing earnings have a larger sensitivity in absolute value to financial shocks. These results are consistent with financial shocks' having an effect on the security prices of nonfinancial firms through financial intermediaries' net worth, which under short-run trading frictions can translate into different prices for bonds with similar risk (see Morelli et al, 2021).…”
Section: Robustness and Placebo Testssupporting
confidence: 78%
“…They specialize in lending to nonfinancial firms. To finance these loans, intermediaries can also raise external finance from households in the form of deposits, d i1 , and equity, x i0 , both of which are subject to frictions, modeled following the literature of frictional financial intermediaries (e.g., Gertler and Kiyotaki, 2010;Morelli et al, 2021). On the deposit side, intermediaries face limited liability constraints, which link their deposits to their net worth: d i1 ≤ κn i0 , with κ ≥ 0.…”
Section: A1 Environmentmentioning
confidence: 99%
“…The existing research, such as Lizarazo (2009) and Borri and Verdelhan (2011), has shown that allowing risk-averse lenders leads to an additional risk premium in sovereign bond pricing. Recent work by Morelli et al (2021) and further examines the role of global financial risk in accounting for the comovements in sovereign spreads. We now turn to a simple model to illustrate the empirical results shown earlier.…”
Section: Interpretation Of the Resultsmentioning
confidence: 99%
“…1 First, Borri and Verdelhan (2011) and Lizarazo (2009) introduce risk-averse lenders into the structural model of sovereign default to generate additional risk premia on sovereign debt beyond the default frequency. and Morelli et al (2021) further study global risk and the financial capacity of international financial intermediaries as determinants of sovereign spread dynamics in quantitative models. Compared to these papers, we examine the impact of global financial risk on sovereign bond spreads using three broad measures of global financial conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, our findings are related to numerous studies analyzing how exchange rate movements affect the terms of trade of a country and, therefore, domestic firms. 9 currency sovereign bonds are those by Borri and Shakhnov (2018), Hofmann et al (2019), and Morelli et al (2019. Relatedly, Warnock and Warnock (2009) and Kohn (2015) analyze the effects of foreign purchases of U.S. government debt on U.S. sovereign bond yields.…”
Section: Introductionmentioning
confidence: 99%